The Center for Research for Peace (Journal of Parents and Teachers, 2025)
The article is based on the information gathered by the Center for Research for Peace, a private, non-governmental, independent, and non-profit organization dedicated to researching political issues, security, ecology, and economics. Given this context, two ways to present images of the Third World are proposed, along with a list of tasks that can be performed with an image.
Keywords: organization; research; images